Протолитические равновесия тиофлуоресцеина в водно-органических смесях - Водолазкая, Н.А.; Саламанова, Н.В.; Мчедлов-Петросян, Н.О. (Інститут загальної та неорганічної хімії ім. В.І. Вернадського НАН України, 2008)
При помощи спектрофотометрического метода определены термодинамические значения pKa трехступенчатого кислотно-основного равновесия тиофлуоресцеина (H3R+ « H2R «HR–« R2–) в водно-этанольных и
водно-ацетоновых смесях. В средах, обогащенных органическим растворителем, нейтральная форма тиофлуоресцеина существует преимущественно в виде бесцветного лактона. Поведение тиоксантеновых красителей удается описать с помощью детальной схемы протолитических равновесий, ранее предложенной для
ксантеновых красителей. На основании электронных спектров поглощения сделаны выводы о таутомерии молекулярной и ионных форм; оценены доли таутомеров и микроскопические константы диссоциации. The thermodynamic pKa values of
stepwise dissociation of thiofluorescein (H3R+ « H2R «
HR–« R2–) in water—ethanol and water—acetone mixtures
were determined by visible spectroscopy. The ratios
of the stepwise dissociation constants of the substance in
mixed solvents, Ka0, Ka1 and Ka2, were compared with those
for fluorescein. The changes of these constants on transferring
from water to mixed solvents are explained taking
into account the nature of functional groups and of the
state of tautomeric equilibria. The conversion of neutral
form of thiofluorescein into colorless lactone in organic
solvent-rich media is demonstrated. Conclusions concerning
tautomerism of the molecular and ionic species were deduced
from the absorption spectra; the fractions of tautomers
as well as microscopic dissociation constants have been
evaluated. The detailed scheme of protolytic equilibria,
developed and proved for xanthene dyes, is shown to be
quite valid for the unsubstituted thioxanthene dye. За допомогою спектрофотометричного методу визначено термодинамічні значення pKa трьох-ступеневої кислотно-основної дисоціації тіофлуоресце- їну (H3R+ « H2R «HR– « R2–) у водно-етанольних і водно-ацетонових сумішах. У середовищах, які збагачені органічним розчинником, нейтральна форма тіофлу- ресцеїну існує переважно у вигляді безбарвного лактону. На основі спектрів поглинання зроблено висновки про таутомерію молекулярної та йонних форм; оцінено частки таутомерів і мікроскопічні константи. За допомогою детальної схеми протолітичних рівноваг, яку раніше було запропоновано для ксантенових барвників, можна описати поведінку тіоксантенових барвників.